Individuals' Long Term Use of Cognitive Behavioural Skills to Manage their Depression: A Qualitative Study - French, L; Thomas, L; Campbell, J; Kuyken, W; Lewis, G; Williams, C; Wiles, N; Turner, K (Cambridge University Press, 2016)
Cognitive Behavioural Therapy (CBT) aims to teach people skills to help them self-manage their depression. Trial evidence shows that CBT is an effective treatment for depression and individuals may experience benefits long-term. However, there is little research about individuals' continued use of CBT skills once treatment has finished.To explore whether individuals who had attended at least 12 sessions of CBT continued to use and value the CBT skills they had learnt during therapy.Semi-structured interviews were held with participants from the CoBalT trial who had received CBT, approximately 4 years earlier. Interviews were audio-recorded, transcribed and analysed thematically.20 participants were interviewed. Analysis of the interviews suggested that individuals who viewed CBT as a learning process, at the time of treatment, recalled and used specific skills to manage their depression once treatment had finished. In contrast, individuals who viewed CBT only as an opportunity to talk about their problems did not appear to utilize any of the CBT skills they had been taught and reported struggling to manage their depression once treatment had ended.Our findings suggest individuals may value and use CBT skills if they engage with CBT as a learning opportunity at the time of treatment. Our findings underline the importance of the educational model in CBT and the need to emphasize this to individuals receiving treatment.